Non-alloy/alloy transitions in the Sn/Cu(001) system: An STM, LEED and DFT study - Machain, Paloma (2017)
We show that surface alloying during growth of Sn on Cu(001) is inhibited at temperatures below 170 K. We have studied the non-alloying surface structures that are formed starting from low Sn coverage up to 0.65 ML, finding two novel non-alloying surface reconstructions. They were investigated by scanning tunneling microscopy (STM) and low energy electron diffraction (LEED) experiments, and by density functional theory (DFT) calculations. Increasing the temperature, we found that the exchange process is activated at 200–240 K causing the transformation of the initial non-alloyed surface into the corresponding alloyed one. The five known reconstructions of the Sn/Cu(100) surface alloy in the studied Sn coverage range are recovered when starting from the low temperature non-alloying phases. We analyze the atomistic processes involved in the non-alloy/alloy transitions, using first-principles calculations of the energy landscape of the Sn/Cu(001) system.